Exploring the possible interlinked structures in single‐wall carbon nanotubes under pressure by Raman spectroscopy. (5th September 2012) - Lu, Shuangchen; Yao, Mingguang; Li, Quanjun; lv, Hang; Liu, Dedi; Liu, Bo; Liu, Ran; Jiang, Linhai; Yao, Zhen; Liu, Zhaodong; Zou, Bo; Cui, Tian; et al.
<x xml:space="preserve">Abstract</x> High‐pressure Raman measurements on single‐wall carbon nanotubes (SWNTs) have been carried out in a diamond anvil cell by using two wavelength lasers: 830 and 514.5 nm. Irrespective of using a pressure transmitting medium (PTM) or not, we found that nanotubes undergo similar transformations under pressure. The pressure‐induced changes in Raman signals at around 2 and 5 GPa are attributed to the nanotube cross‐section transitions from circle to ellipse and then to a flattened shape, respectively. Especially with pressure increasing up to 15–17 GPa, we observed that the third transition takes place in both the Raman wavenumber and the linewidth of G‐band. We propose explanations that the interlinked configuration with sp3 bonds forms in the bundles of SWNTs under pressure, which was the cause for the occurrence of those Raman anomalies, similar to the structural‐phase transition of graphite above 14 GPa. Our TEM observations and Raman measurements on the decompressed samples support this transition picture. Copyright © 2012 John Wiley & Sons, Ltd.